Online Learning Policies and Indonesian Language Learning Constraints during the Covid-19 Pandemic - Muhammad Agung Wibisono; Hartono Hartono (Randwick International of Education and Linguistics Science Journal, 2021)
This research aims to analyze online learning policies and the problems of obstacles of teachers, learners, and parents in learning Indonesian in the covid-19 pandemic. This type of research is a case study at Muhammadiyah 4 Yogyakarta Junior High School and literature study using secondary data collected through books, journals, websites, and other sources related to research problems. Data collection uses interview techniques and document analysis. Data analysis uses qualitative descriptive techniques, consisting of data collection and subtraction, data presentation, and conclusion withdrawal. The results showed that the distance learning policy implemented at Muhammadiyah Junior High School 4 Yogyakarya was in accordance with the Circular Letter (SE) of the Ministry of Education No. 4 of 2020 on the Implementation of Education Policy in the Emergency Period of The Spread of Coronavirus Disease (COVID-19). The policies implemented include policies to provide student learning experiences, provide life skills education, learning in accordance with student conditions, the process of awarding assessments, and the process of Admission of New Learners (PPDB) and School Operational Assistance (BOS). On the other hand, there are also learning obstacles for teachers, learners, and parents in Indonesian learning experienced during the diverse covid-19 pandemic. Teacher constraints are on aspects of the use of learning applications, weak internet network access, unpreparedness with online learning media, learning materials that cannot be applied optimally, and research to learners. Student constraints are on aspects of inadequate learning facilities, weak internet access, inactivity in following learning, psychological conditions of stress and boredom, many tasks, and difficulties in operating learning applications. Parental constraints are on socio-economic aspects and supervision or mentoring of children in online learning at home.